Metal vaporization and its influence during laser powder bed fusion process. (March 2022) - Liu, Jinge; Wen, Peng
Graphical abstract: Highlights: It is the first review article on the metal vaporization during LPBF or other high energy beam manufacturing processes. Metal vaporization during the LPBF from the aspect of mechanism, influence and numerical simulation was summarized roundly. For a deep understanding of metal vaporization under high energy beam, laser welding and EBPBF were referred to make a comparison with LPBF. How to control and utilize metal vaporization during LPBF was pointed out in this article. Abstract: Laser powder bed fusion (LPBF) is a key metal additive manufacturing process and has attracted increasing attention both in academia and industry. An essential physical issue influencing LPBF is metal vaporization, and there has been much dispute regarding the occurrence and influence of metal vaporization during LPBF. The latest in-situ X-ray imaging results directly demonstrated the occurrence of massive vaporization based on the widespread presence of keyholes under typical LPBF conditions. In this study, a comprehensive review of metal vaporization during LPBF was conducted, in terms of its influence and underlying mechanism, as well as numerical simulations. Metal vaporization was found to be primarily dependent on the temperature of the melt pool and the surrounding atmosphere, and to substantially influence the transfer of energy, momentum, and mass during the process. Critical formation problems, such as powder denudation, plume, spatter, lack of fusion, and porosity were closely related to metal vaporization. An adequate energy input and optimized shielding atmosphere were found to be necessary to inhibit the negative influence of metal vaporization. Moreover, the vaporization by-products could be used for quality monitoring, and the vaporization loss of elements could be quantitatively adjusted to regulate the compositional distribution.